PENGARUH TUNTUTAN PEKERJAAN TERHADAP CYBERLOAFING DENGAN KEBOSANAN KERJA SEBAGAI MEDIATOR PADA KARYAWAN YANG BEKERJA DARI RUMAH - Elfira Pipit Kurniawati; Rostiana Rostiana; Rita Markus Idulfilastri (Jurnal Psikologi, 2023)
The policy of working from home during the COVID-19 pandemic caused changes in the work environment and job demands that were suspected of causing cyberloafing. This study aims to determine the role of job boredom in mediating the effect of job demands on cyberloafing. Data were collected through online questionnaires to measure cyberloafing, job boredom and job demands from 116 participants who work as administrative staff. Data processing was carried out through regression techniques. The results showed that job demands had a significant effect on cyberloafing (β = 0.427, p = 0.000). After entering job boredom as a mediator, the results showed that the effect of job demands on cyberloafing decreased (β = 0.251, p = 0.004). These results indicate that job boredom can mediate (partially) the effect of job demands on cyberloafing. So, the effect of job demands on cyberloafing is even greater when those demands lead to work boredom. The  correlation between demographic data and research variables show that position, working hours and length of using internet  have a positive correlation with job demands; age, tenure, and working hours have a negative correlation with job boredom; age and tenure are negatively correlated with cyberloafing.